Melampaui Tantangan Daerah Terpencil : Mengupas Kinerja Pegawai Kantor Kampung Yefman Barat dalam Peningkatan Disiplin - Meisarah, Marnisah; Tumoka, Isgar Muhammad Ricky; Nurhidaya; Ramli, Umar (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2024)
Discipline in the workplace is very important for organizations because without discipline there will be no constructive joint efforts to achieve common goals. The Yefman Office is one of the spearheads of community service on Yefman Island. Its services require employees who are professional and competent in dealing with work pressure. This research aims to investigate the performance of employees at the West Yefman Village Office, a remote area, to improve discipline in their work environment. Employee discipline is a key factor in achieving efficiency and effectiveness in carrying out government tasks. The results of this research provide a better understanding of the challenges and opportunities faced by employees in remote areas such as West Yefman Village. The implication of this research is the importance of developing better infrastructure, training, and incentive systems to improve employee discipline and, in turn, improving government performance in remote areas.